Better predictive value of axillary lymph node (ALN) status after systemic therapy for operable HER2-overexpressing breast cancer: A single-institution retrospective study. Issue 8 (August 2016) - Zhang, Y.; Mo, M.; Li, J.-w.; Zhou, Y.; Wu, J.; Yu, K.-d.; Shen, Z.-z.; Shao, Z.-m.; Liu, G.-y.
Abstract: Background: Thresholds for using Preoperative Systemic Therapy (PreST) have decreased to include early breast cancer. This study investigates the predictive value of axillary lymph node (ALN) status before and after systemic therapy and discusses whether it is better to receive PreST first in operable HER2-overexpressing breast cancer patients. Methods: From January 2008 to June 2013 at Fudan University Shanghai Cancer Center, we identified 406 eligible female patients with stage II-IIIa, operable and pathologically confirmed HER2-overexpressing invasive ductal carcinoma. Of these patients, 269 underwent surgery first followed by chemotherapy plus trastuzumab (chemo-trastuzumab) (SurgFirst group), whereas 137 received systemic chemo-trastuzumab therapy first followed by surgery (STFirst group). Disease-free survival (DFS) and overall survival (OS) were evaluated according to different ALN statuses using the Kaplan–Meier method. Multivariate COX model analyses were also conducted. Results: The median follow-up time was 47 months (IQR: 37–60). Both ALN status and overall pathological complete remission (pCR) status were shown to be significant for the prediction of DFS ( p  = 0.001 and p  = 0.005, respectively) and OS ( p  = 0.009 and p  = 0.027, respectively) in the STFirst group. However, patients with positive ALN(s) did not experience significantly poorer survival compared with those with negative ALN in the SurgFirst group. The adjusted hazard ratios (HRs) for positive ALN status in the STFirst and SurgFirst groups were 6.66 ( p  = 0.001, 95%CI: 2.18–20.38) and 2.40 ( p  = 0.126, 95%CI: 0.78–7.34), respectively. Conclusion: The ALN status after systemic chemo-trastuzumab therapy better predicts the survival outcome. We recommend the application of PreST followed by surgery in patients with operable HER2-overexpressing breast cancer.